The ineffectiveness of counterclaim advertising for increasing consumer sentiment. Issue 1 (23rd August 2016) - Coker, Brent
Abstract: When a brand is disliked, one strategy used to improve consumer sentiment is to make counter‐claims against the reason for dislike. But little is known about the effectiveness of this strategy, or the effect this strategy has on differential judgements towards the brand. Two experimental studies are conducted to shed light on the effectiveness of counterclaim advertising. The results find evidence to suggest that counter‐claim advertising may actually worsen sentiment towards the brand, when the brand is already disliked. The findings suggest that brands do not try to directly counter known reasons for dislike, but instead formulate alternative ways to rebuild trust. Copyright © 2016 John Wiley & Sons, Ltd.